Mycenaean Civilization : An Annotated Bibliography through 2002 - Feuer, Bryan Avery (McFarland & Company, Inc., Publishers, 2004)
Classical Greeks considered the Mycenaean civilization to be the basis of their glorious and heroic heritage, but its material existence was not confirmed until the excavations of Heinrich Schliemann in the late nineteenth century. In the ensuing years, as with the field of archaeology in general, emphasis has shifted from revealing monuments and finding treasure to dealing with less glamorous, more scientifically-oriented investigations concerning aspects such as social and political organization, economic functions and settlement patterns. With its more than 2000 entries, this reference work